PRODUCTION, PROCESSING, OPTIMIZATION, ORGANIZATION AND IMPROVEMENT OF AGRICULTURAL PRODUCTS IN OUR COUNTRY (European Journal of Economics, Finance and Business Development, 2025)
This is article reflects the importance of organizing clusters of agricultural production and processing in providing employment to the rural population, offers training based on the public-private partnership, as well as the direction of creating new jobs in clusters of agricultural production and processing.